Organização das assembléias de peixes em riachos da bacia do rio Iguatemi, Estado do Mato Grosso do Sul - Súarez, Yzel Rondon; Petrere Jr., Miguel [UNESP] (Universidade Estadual de Maringa, 2005)
Aiming to describe the patterns of the fish assemblages organization in streams of the Iguatemi River basin we sampled streams with seine nets and sieves from November/1999 to August/2000. We collected 567 individuals distributed in 24 species. We detected statistically significant influence of the streams characteristics upon species diversity. The species composition was hardly explained by the physical and chemical characteristics of the streams. Then we detected significant influence of the fish ecomorphology in the species occurrence (Mantel r = -0.34; P = 0.04), but not in the distribution of its abundance (Mantel r = -0.21; P = 0.07). We verified through the species co-occurrence index (C-score) that its composition in the studied streams is stochastic.
Organization of the fish assemblages in streams of Iguatemi River basin, Mato Grosso do Sul State
Keywords: Community ecology; Fishes; Iguatemi River Basin; Streams; Brazil; community ecology; fish; geography; nonhuman; population abundance; river basin; species composition; species diversity; statistical analysis; stream (river); Pisces